Prognostic Value of Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio in Lung Cancer - Seda Beyhan Sagmen; Coskun Dogan; Sevda Comert; Nesrin Kiral; Ali Fidan; Elif Torun Parmaksiz (Medical Laboratory Technology Journal, 2019)
Numerous studies determined that the neutrophil/lymphocyte (NLR) and platelet/lymphocyte ratios (PLR) had prognostic value in several cancer types. This study aimed to evaluate the relationship between NLR and PLR values with the survival time of lung cancer patients. Patients diagnosed with lung cancer between January 2014 and December 2016, were retrospectively evaluated. Demographic characteristics, disease stages, laboratory parameters recorded, and the relationship of NLR and PLR values with the survival time and the disease stage evaluated. NLR and PLR were categorized into two groups. SPSS 17.0 software package was used for the statistical analysis. ROC analysis, Student T-test, Chi-square, and Mann-Whitney U test were used. Mean age of 62±8 years were included in the study. In the NSCLC group, the average NLR and PLR values were 4±3.35 and 194.6±144.4 respectively. Regarding the NSCLC group, the overall survival time was shorter in the subgroup with an NLR >3.43 (13.1 months) compared to the subgroup with an NLR ≤3.43 (24.3 months). The mean survival time was shorter in the group with a PLR > 136.9 compared to the group with a PLR ≤136.9 (15.9 and 24.6 months respectively). Subgroups consisting of survivors and non-survivors in the NSCLC group showed a statistically significant difference considering neutrophil and lymphocyte count, CRP, NLR, and PLR values (p